ANALISIS FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP HARGA SAHAM (Studi Kasus Pada Perusahaan Pertambangan Yang Terdaftar Di BEI Tahun 2011-2013) - Ronal Kresna Wardana, 12.05.52.0077; ., Wardjono (Students Journal of Accounting and Banking, 2015)
This study aimed to examine the effect of Return On Invesment (ROI), Return On Equity (ROE), Price Erning Ratio (PER), Price to Book Value (PBV) dan Current Ratio of stock price category mining companies listed on the Stock Exchange in 2011-2013 listed on the Indonesia Stock Exchange (IDX). The population is the entire company mining in Indonesia Stock Exchange (IDX) with 40 companies and research during the period of 2011 to 2013. Samples taken in this study is 35 companies. The sampling technique used purposive sampling. The analytical tool used in this study is Multiple Linear Regression Analysis. The results showed that the showed that, between Return On Invesment (ROI), Return On Equity (ROE), Price Erning Ratio (PER), Price to Book Value (PBV) dan Current Ratio jointly influence on stock prices. Partial results of hypothesis testing indicates that Return On Investment (ROI) and significant positive effect on stock prices, Return On Equity (ROE), Price erning Ratio (PER), Price to Book Value (PBV) positive effect was not significant and the Current Ratio (CR) significant negative effect.Keywords: Return On Equity (ROE), Net Profit Margin (NPM), Earning Per share (EPS), Cash Ratio and Stock Price